2022
DOI: 10.3390/jtaer17020032
|View full text |Cite
|
Sign up to set email alerts
|

UTAUT in Metaverse: An “Ifland” Case

Abstract: Since 2021, big tech companies have been interested in metaverse platforms and services. Metaverse is the permanent, immersive mixed-reality world where people and people and people and objects can synchronously interact, collaborate, and live beyond the limitations of time and space, using avatars and the immersion-supporting devices, platforms, and infrastructures. On metaverse platforms, people can merge the real world and the virtual world. Because the metaverse has only recently begun to be studied, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…The vision of the Metaverse comprises the idea that an unlimited number of users can experience virtual worlds simultaneously [8]. This attribute is strongly related to the computing power of the platforms running the virtual worlds as well as the bandwidth of connections [7].…”
Section: B) Synchronicitymentioning
confidence: 99%
“…The vision of the Metaverse comprises the idea that an unlimited number of users can experience virtual worlds simultaneously [8]. This attribute is strongly related to the computing power of the platforms running the virtual worlds as well as the bandwidth of connections [7].…”
Section: B) Synchronicitymentioning
confidence: 99%
“…Over time, however, scholars, practitioners, and companies have refined the initial metaverse idea in different directions or developed completely new ones. Thus, even though the metaverse is widely discussed, it lacks a commonly accepted and consistent definition (Lee and Kim 2022;Park and Kim 2022;Xu et al 2022). Yet, the lack of a definition is not surprising at this stage, as only the future will show us what shape it will ultimately take.…”
Section: On the Need To Demystify The Metaversementioning
confidence: 99%
“…As a result of a literature review, Park and Kim (2022) provide a list of metaverse definitions originating from 54 different sources that take reference to the metaverse. Lee and Kim (2022) have further refined and updated the list and retrieved common characteristics within the definitions, namely, avatars as user representation, technology used for world representation (i.e., AR, VR, MR), synchronicity reflecting the real-time component, interactivity with objects, immersion and realism describing the closeness to reality and the ability to experience telepresence, support of social collaboration (i.e., interaction between users), and permanence outlining the continuance and persistence of the metaverse. In Information Systems (IS), the term metaverse has also been around for several years, mostly to capture phenomena around virtual worlds such as Second Life.…”
Section: On the Need To Demystify The Metaversementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that satisfaction has a significant impact on the willingness of a player to continue using some platforms, such as mobile shopping apps, metaverse platform, online social networks, and book self-service systems ( Natarajan et al, 2017 ; Wu and Wu, 2018 ; Lee and Kim, 2022 ). Satisfaction with the mobile shopping application environment is the sum of emotional responses to mobile shopping application activities triggered by various factors, such as information, system, and service quality ( Agrebi and Jallais, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%